(untitled) (Journal of Enam Medical College, 2017)
Background: Though paediatric spinal anaesthesia has been used since early 20th century in developed countries even in neonates, still it is not common in our country. Spinal anaesthesia can be given in neonates and children for infraumbilical surgeries with an expert and experienced anaesthesiologist. Objective: The objective of this study was to establish spinal anaesthesia as a safe and effective regional anaesthetic procedure in children of 410 years. Materials and Methods: The study was done in the Department of Anaesthesiology & Intensive Care Unit of Enam Medical College & Hospital during the period of June 2012 to May 2014. A total of 102 patients aged from 4 to 10 years with American Society of Anaesthesiologists (ASA)-I and II were selected. After proper preoperative anaesthetic evaluation spinal anaesthesia was administered. All patients were premedicated with atropine, preloaded with crystalloid solution and sedated with ketamine 1 mg/kg or midazolam 0.03 mg/kg. 0.5% hyperberic bupivacaine was injected at L4/5 or L5/S1 level with spinocaine needle. After establishment of desired block, surgery was performed. All vital parameters, number of attempts for lumbar puncture, sensory and motor block were monitored and recorded. Results: Almost all patients achieved desired block (T8T10) within 5 to 10 minutes. The success rate in our study was 96.1% and remaining 3.9% were considered as failure. No remarkable changes were observed in vital parameters after spinal anaesthesia. Lumbar puncture was successful in first attempt in 60 (58.82%) cases and in second attempt in 42 (41.18%) cases. Hypotension occurred in 2%, shivering in 3% and 3% developed restlessness. Conclusion: Spinal anaesthesia produces a reliable, profound and uniformly distributed block with rapid onset, good muscle relaxation, complete control of cardiovascular and stress responses compared with epidural or GA. There is also rapid recovery and minimal complications without special drugs or expensive equipments. However, greater acceptance and experience are still desired for this technique to become more popular. J Enam Med Col 2017; 7(1): 10-14